Employment Opportunity of Community College Students in Local Market Kirtipur - Mahataman, Tribhuvan Kumar (Shahid Kirti Multidisciplinary Journal, 2024)
This paper seeks to explore the association between community college student and local market, to examine the relationship between community college and local market and to analyze the impact of hiring community college student. on local business sectors. The study uses primary sources and questionnaires to gather data on Community, community college student and local business houses in Kirtipur. Total population is 260, a sample size of 159 was used, with 16 questions categorized into five rating parameters: strongly disagree (SD), disagree (D), neither disagree nor agree (N), agree (A), and strongly agree (SA). The descriptive, inferential statistic and purposive sampling research design was followed. There is significant relationship between community college and local market. There is significant impact of hiring community college student on local business sectors. There is significant association between community college student and local market.